Negative Public Perception and Reoffending of Discharged Offenders in Anambra State, Nigeria - NWAFOR, Kenechukwu C.; OGUAMANAM, Gabriel O.; OSAYI, Kelechi K. (Socialscientia: Journal of Social Sciences and Humanities, 2022)
Crime is a menace to the society. Its impact has led to negative predisposition of the public towards its perpetrators. This has led to the formulation of laws that address criminal activities and their perpetrators. Thus, society has made provisions for facilities such as the Criminal Justice System (Police, Law court, Correctional Centers) that helps to process and reform these offenders. However, the perception of the public towards discharged offenders appears to remain the same as when the crime was committed and this negative perception has, in most cases, led to the reoffending of discharged offenders. The present study examined the effects of negative public perception of discharged offenders on their reoffending in Anambra State. The study adopted a mixed method research design using questionnaire schedule and In-Depth Interview guide as the instruments of data collection. The study drew a sample size of 400 from the total population of Anambra state. Data was analyzed electronically using descriptive statistics and expressed in frequency tables and simple percentages. The study revealed among others, numerous social consequences faced by discharged offenders as a result of the negative perception held against them which in turn make them to reoffend. It was recommended among others, that discharged offenders should be allowed to engage in community social services that will benefit their community as this will help convince community members that discharged offenders are now changed functional members of the society.